Speech Acts on Discourse Analysis Used in a Speech “What Really Matters at the End Life” by BJ Miller - Popiana Br Hutauruk; Jesana Tessalonika Simaremare; Astrinia Ristama Tampubolon; Albert Welman Daulat Lumbangaol; David Suranta Sinamo; Herman Herman (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to analyze and identify the contents of the speech